Оценка влияния ионосферных бурь на ионосферные каналы распространения радиоволн по данным наблюдения на харьковском радаре некогерентного рассеяния - Кацко, Софья Валериевна; Черногор, Леонид Феоктистович (НТУ "ХПИ", 2015)
Оценено влияние ионосферных бурь на ионосферные каналы распространения радиоволн. Подтверждено, что вариации параметров ионосферы во время ионосферных бурь вызывают существенную перестройку каналов распространения радиоволн, а основные характеристики радиоволн (фаза, амплитуда и др.) при этом значительно изменяются. Проведен расчет изменения частоты соударений электронов с ионами, показателя поглощения радиоволн и частотной емкости ионосферного канала для отрицательных и положительных ионосферных возмущений во время магнитных бурь 1998–2012 гг.

The ionospheric storms influence on ionosphere radio waves propagation channel is estimated. It is confirmed, that ionosphere parameters variations during ionospheric storms cause essential reconstruction of the radio waves propagation channel and at that main parameters of radio waves (phase, amplitude et al.) change. The calculation of variations of the electrons and ions collision frequency, the index of radio wave absorption and the frequency capacity of ionosphere channel for negative and positive ionospheric disturbances during magnetic storms of 1998–2012 are performed.
Estimation of the ionospheric storms influence on ionosphere radio waves propagation channel by the observation data at the Kharkiv incoherent scatter radar
Keywords: ионосфера; коэффициент поглощения; частота соударения; частотная емкость; ionosphere; ionosphere storm; radio waves propagation channel; index of absorption; collision frequency; frequency capacity